2016
DOI: 10.1128/aac.03059-15
|View full text |Cite
|
Sign up to set email alerts
|

Garcinol Inhibits GCN5-Mediated Lysine Acetyltransferase Activity and Prevents Replication of the Parasite Toxoplasma gondii

Abstract: Lysine acetylation is a critical posttranslational modification that influences protein activity, stability, and binding properties. The acetylation of histone proteins in particular is a well-characterized feature of gene expression regulation. In the protozoan parasite Toxoplasma gondii, a number of lysine acetyltransferases (KATs) contribute to gene expression and are essential for parasite viability. The natural product garcinol was recently reported to inhibit enzymatic activities of GCN5 and p300 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Garcinol treatment led to decreased levels of acetylated histone H3 of TgGCN5b and to an inhibition of replication (IC 50 =1.7 μM). Similar replication inhibitory effects were observed for the malaria parasite Plasmodium falciparum (IC 50 =1.69 μM for chloroquine‐sensitive HB3 strains, and IC 50 =2.05 μM for chloroquine‐resistant Dd2 strains; inhibition of erythrocytic asexual replication) …”
Section: An Update On the Activities Of Garcinol Against Viruses Bacsupporting
confidence: 72%
See 2 more Smart Citations
“…Garcinol treatment led to decreased levels of acetylated histone H3 of TgGCN5b and to an inhibition of replication (IC 50 =1.7 μM). Similar replication inhibitory effects were observed for the malaria parasite Plasmodium falciparum (IC 50 =1.69 μM for chloroquine‐sensitive HB3 strains, and IC 50 =2.05 μM for chloroquine‐resistant Dd2 strains; inhibition of erythrocytic asexual replication) …”
Section: An Update On the Activities Of Garcinol Against Viruses Bacsupporting
confidence: 72%
“…Similar replication inhibitory effects were observed for the malaria parasite Plasmodium falciparum (IC 50 = 1.69 μM for chloroquine-sensitive HB3 strains, and IC 50 = 2.05 μM for chloroquine-resistant Dd2 strains; inhibition of erythrocytic asexual replication). [63]…”
Section: An Update On the Activities Of Garcinol Against Viruses Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…We may be able to add infections caused by protozoan parasites to this list, as genetic studies have shown that most parasite bromodomain proteins are crucial for viability and virulence. Some studies have already begun to examine the effects of bromodomain inhibitors against these protozoan parasites, and these complement previous work showing the antiparasitic activities of KAT and KDAC inhibitors (55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Bromodomain Inhibition In Protozoan Parasitesmentioning
confidence: 48%
“…Host cell toxicity remains a concern with compound 34; the TD 50 for human host cells is less than 10 times greater than the IC 50 for T. gondii, but compound 35 seems to fare better on host cells with a TD 50 of Ͼ10 M in HS68 cells (74,77) (Table 1). Garcinol, derived from the Garcinia indica fruit, is another compound that affects histone acetylation, targeting a family of lysine acetyltransferases (KAT) enzymes required for T. gondii tachyzoites to replicate successfully (78). Additionally, other (nonhistone) substrates of these compounds may be affected, contributing to the overall host cell toxicity and to the efficacy of the compound against the parasite (79).…”
Section: Inhibition Of Transcriptionmentioning
confidence: 99%